2018
DOI: 10.1103/physrevd.97.105020
|View full text |Cite
|
Sign up to set email alerts
|

Nonrelativistic limits of colored gravity in three dimensions

Abstract: The three-dimensional nonrelativistic isometry algebras, namely Galilei and Newton-Hooke algebras, are known to admit double central extensions, which allows for nondegenerate bilinear forms hence for action principles through Chern-Simons formulation. In three-dimensional colored gravity, the same central extension helps the theory evade the multigraviton no-go theorems by enlarging the color-decorated isometry algebra. We investigate the nonrelativistic limits of three-dimensional colored gravity in terms of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Thus, our synthesised RGO-ZnS system may be considereda s ah eterogeneous mixture of high conducting sp 2 functionalised RGO sheets and insulating sp 3 functionalised GO sheets. [15,16] The well separated sp 2 graphene domains are illustrated in Figure2Afor which the void white regions are the insulating sp 3 domains (left). Thes ize of sp 2 graphene domains increases owing to the photocatalytic reduction of GO by ZnS,w hich effectively decreases the separation among the sp 2 domains (right).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, our synthesised RGO-ZnS system may be considereda s ah eterogeneous mixture of high conducting sp 2 functionalised RGO sheets and insulating sp 3 functionalised GO sheets. [15,16] The well separated sp 2 graphene domains are illustrated in Figure2Afor which the void white regions are the insulating sp 3 domains (left). Thes ize of sp 2 graphene domains increases owing to the photocatalytic reduction of GO by ZnS,w hich effectively decreases the separation among the sp 2 domains (right).…”
Section: Resultsmentioning
confidence: 99%
“…The low-temperature transport in RGO is dominated by coulomb blockade and variable-range hopping conduction mechanism and also by the sp 2 fractions present in the RGO matrix. [15,16] Park et al observed the ES variable-range hopping electrical conduction mechanism in RGO-polystyrene composites. [17] Althought here are few reports on electronic conduction mechanism in RGO based systems, all the studies are confined to DC electricalm easurements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For interesting Chern-Simons theories that go beyond or generalize the kinematical setup, see, e.g., [35][36][37][47][48][49].…”
Section: Kinematical Limits Of Three-dimensional Gravitymentioning
confidence: 99%